Analysis Of Factors That Influence Patient Satisfaction In The Inpatient Installation Manembo-nembo Type C Hospital Bitung - Pradika Hanrianri Koampa; Aaltje E. Manampiring; Eva M. Mantjoro (Lead Journal of Economy and Administration, 2023)
ccording to the World Health Organization (WHO) Hospital is a medical institution that functions as a provider of curative and rehabilitative health service to the community. Hospital is a health institution that provides comprehensive health services in the form of emergency, outpatient, and inpatient. According to its type, hospitals are devided into Special Hospitals and General Hospitals. Then General Hospitals are devided into Type A, Type B, Type C, and Type D. Satisfaction is a person’s feelings towards the comparison of the results recived and his expectations. The level of patient satisfaction is caused by several factors namely reliability, tangibles, responsiveness, empathy, and assurance. This research is an analytic observational survey research with cross sectional approach. The population of this study were patients who were temporarily treated in the inpatient room of Manembo-nembo Type C Hospital, Bitung. The determination of the research sample was carried out using the accidental sampling method. The total number of samples obtained was 70 people. The variable that is significantly related to inpatient satisfaction are reliability (p value = 0,000), tangibles (p value = 0,000), responsiveness (p value = 0,000), empathy (p value = 0,000), and assurance (p value = 0,000). There is a relationship between reliability, tangibles, responsiveness, empathy, and assurance for patient satisfaction at Manembo-nembo Type C Hospital , Bitung.